Structures of Fear, Spaces of Hope - Carbonella, August (Anthropologica, 2022)
Fear, as Mary Douglas long ago observed, is centrally a concern with boundaries and their transgression. In this article, I explore the politics of boundary maintenance and transgression in the cauldron of the American War in Vietnam. Drawing primarily upon the war crimes testimony, memoirs and oral histories of U.S. soldiers and veterans of the Vietnam era detailing their dissent and shifting loyalties, I argue that boundary transgression, contrary to Douglas' influential deep structural analysis, is an important means of establishing countervailing forms of power. Further, the multiple challenges that these soldiers and veterans posed to the expansion of the American empire allow us to view boundaries and transgression not as opposite poles to be contemplated but rudiments of a ferocious encounter between fear and hope.